Implementasi Metode Runge-Kutta dalam Simulasi Lintasan Peluru pada Medan Gravitasi Bumi - Vena Yurinda Saragih; Giovani Br Surbakti; Nia Elovani Br Munthe; Syabila Amalia Wardani (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This study examines the implementation of the fourth-order Runge-Kutta method in simulating bullet trajectories in the Earth's gravitational field. Bullet trajectory simulation is important in various fields such as ballistics and engineering, where the accuracy of predicting the trajectory of a moving object is crucial. The introduction explains the importance of using numerical methods in solving complex equations of motion, considering that analytical solutions are often inadequate. The purpose of this study is to apply the Runge-Kutta method to solve nonlinear differential equations describing the motion of a bullet under the influence of gravity. The research methods include modeling the motion system using Newton's laws and applying the Runge-Kutta method to predict the trajectory based on initial conditions such as velocity and firing angle. The simulation results show that the Runge-Kutta method provides accurate predictions of bullet trajectories, with low relative errors compared to other numerical methods. In conclusion, this method is effective and efficient in simulating bullet trajectories, providing reliable results in practical applications.